Alpha Globin Gene Copy Number Is Associated with Prevalent Chronic Kidney Disease and Incident End-Stage Kidney Disease among Black Americans. Issue 1 (January 2022) - Ruhl, A. Parker; Jeffries, Neal; Yang, Yu; Naik, Rakhi P.; Patki, Amit; Pecker, Lydia H.; Mott, Bryan T.; Zakai, Neil A.; Winkler, Cheryl A.; Kopp, Jeffrey B.; Lange, Leslie A.; Irvin, Marguerite R.; et al.
Significance Statement: Resistance artery endothelial cells express α -globin, which limits nitric oxide signaling and enhances α -adrenergic–mediated vasoconstriction—two signaling pathways involved in renal blood flow regulation and kidney disease pathogenesis. A common HBA gene deletion might therefore confer protection against kidney disease by increasing endothelial nitric oxide signaling and decreasing vasoconstriction in response to α -1–adrenergic stimuli. Among Black Americans, HBA copy number varied from 2 to 6; an increase by one HBA gene copy was associated with 14% greater risk of CKD and 32% greater hazard of incident ESKD. This study identifies HBA deletions as protective against CKD and ESKD and highlights the importance of understanding the role of α -globin in renovascular pathophysiology. Visual Abstract: Abstract : Background: α -Globin is expressed in endothelial cells of resistance arteries, where it limits endothelial nitric oxide signaling and enhances α -adrenergic–mediated vasoconstriction. α -Globin gene ( HBA) copy number is variable in people of African descent and other populations worldwide. Given the protective effect of nitric oxide in the kidney, we hypothesized that HBA copy number would be associated with kidney disease risk. Methods: Community-dwelling Black Americans aged ≥45 years old were enrolled in a national longitudinal cohort from 2003 through 2007. HBA copy number was measured using droplet digital PCR. The prevalence ratio (PR) of CKD and the relative risk (RR) of incident reduced eGFR were calculated using modified Poisson multivariable regression. The hazard ratio (HR) of incident ESKD was calculated using Cox proportional hazards multivariable regression. Results: Among 9908 participants, HBA copy number varied from 2 to 6. In analyses adjusted for demographic, clinical, and genetic risk factors, a one-copy increase in HBA was associated with 14% greater prevalence of CKD (PR, 1.14; 95% CI, 1.07 to 1.21; P <0.0001). While HBA copy number was not associated with incident reduced eGFR (RR, 1.06; 95% CI, 0.94 to 1.19; P =0.38), the hazard of incident ESKD was 32% higher for each additional copy of HBA (HR, 1.32; 95% CI, 1.09 to 1.61; P =0.005). Conclusions: Increasing HBA copy number was associated with a greater prevalence of CKD and incidence of ESKD in a national longitudinal cohort of Black Americans.